Achievement Emotion during Class and Its Impact on the Use of Learning Strategies - ., Sunawan; ., Sugiyo; Kurniawati, Yuli (KnE Social Sciences, 2019)
The purpose of present study was to investigate the impact of achievement emotions during Statistics Class on the use of learning strategies. This study involved 339 of undergraduate students of Faculty of Education, Universitas Negeri Semarang, who take the statistics class. The hierarchical regression analysis showed that students’ enjoyment positively predicted the use of rehearsal, elaboration, and organization learning strategies. In contrast, not all negative emotions have correlation with the use of learning strategies. Boredom positively predicted the use of rehearsal, but negatively predicted the use of elaboration. Then, angry negatively predicted the use of rehearsal. Findings of present study asserted the importance of enjoyment during class to encourage students use the appropriate and adaptive learning strategies. Keywords: achievement emotions; learning strategies